High-performance transparent self-repairing conductive elastomer and preparation method thereof

By introducing the oxygen atomic coordination of lithium ions and carbonyl groups into the polyurethane-urea elastomer and the cation-π interaction of lithium ions and benzene rings, combining multiple hydrogen bonds to build a polymer network, flexible stretchable conductors are solved The problem of insufficient mechanical properties and self-repair capabilities of the material achieves high-performance conductive and self-repair functions.

CN119119413AActive Publication Date: 2024-12-13SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411195769.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The existing flexible stretchable conductor materials have problems such as water loss drying, ionic liquid leakage, low mechanical properties and insufficient self-repair capabilities during use, which limits their application in open environments and wearable electronic devices in human bodies.

Method used

By introducing the oxygen atomic coordination between lithium ions and carbonyl groups and the cation-π interaction between lithium ions and benzene rings in the polyurethane-urea elastomer, combining multiple hydrogen bonds to build a polymer network, and preparing a high conductivity , Polyurethane-urea conductive elastomer with high strength, excellent rebound properties, self-healing properties and transparency.

Benefits of technology

It has achieved high tensile strength (68.7MPa), high light transmittance (91.01%), high ionic conductivity (1.32×10-5S/cm) and excellent self-repair ability, and is suitable for monitoring of dynamic human activities and mechanical movements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005016331890000071
    Figure BDA0005016331890000071
  • Figure BDA0005016331890000091
    Figure BDA0005016331890000091
  • Figure BDA0005016331890000101
    Figure BDA0005016331890000101
Patent Text Reader

Abstract

The invention belongs to the technical field of transparent self-repairing conductive elastomer materials, and discloses a high-performance transparent self-repairing conductive elastomer and a preparation method thereof. The method comprises the following steps: 1) reacting polyester diol with diisocyanate under the action of a catalyst to obtain an isocyanato-terminated polyurethane prepolymer; 2) mixing benzene ring-containing dihydrazide with the polyurethane prepolymer, carrying out chain extension reaction, adding bis (trifluoromethanesulfonyl) lithium imide, and carrying out curing molding to obtain a polyurethane-urea conductive elastomer; the dihydrazide is one or more of isophthalic acid dihydrazide or terephthalic acid dihydrazide. The method disclosed by the invention is simple, and the obtained elastomer material has high transparency, high mechanical property and better self-repairing performance; meanwhile, the material has good conductivity and excellent stretching resilience, can be used as an excellent stretchable conductor material, and has huge application potential in the aspects of monitoring human body dynamic activities, monitoring mechanical movement, monitoring a man-machine interaction process and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive elastomer materials, and in particular relates to a high-performance transparent self-healing conductive elastomer and a preparation method thereof. Background Art

[0002] With the rapid development of flexible electronic materials, flexible and stretchable conductors with intrinsic stretchability, conductivity and good resilience are indispensable basic materials for the development of flexible electronic devices. Stretchable conductor materials can be divided into three types: hydrogels, ion gels and ion conductive elastomers. The problems of dehydration and low mechanical properties of hydrogels hinder the practical use of hydrogel-based electronic devices in open environments. Ion gels have the problem of leakage of highly toxic ionic liquids after compression and tensile deformation, which hinders the practical application of ion gels in wearable electronic devices and limits the long-term stable service of ion gel-based electronic devices. As one of the stretchable conductors, ion conductive elastomers have become a reliable alternative to gel-based ion conductors, solving the disadvantages of dehydration and ion liquid leakage of the former, but they still have the disadvantage of relatively low mechanical properties, which is easy to break during use, and eventually lead to the failure of flexible electronic devices. Therefore, the main goal of further developing such materials is to simultaneously improve the mechanical properties and self-healing properties of the materials on the basis of introducing ionic conductivity and intrinsic stretchability, prepare a high-performance self-healing ion conductive elastomer material, and realize the high performance and conductive functionalization of self-healing elastomers.

[0003] Chinese invention patent CN 116496436 A discloses a preparation method and application of a multi-hydrogen bond network-based self-healing highly transparent conductive elastomer. By constructing a choline chloride / acrylic acid-imidazolidinyl urea-based polymerizable low eutectic solvent system and introducing a dense hydrogen bond network, the elastomer material is endowed with good conductivity, mechanical properties, self-healing properties and transparency, with a tensile strength of 1.02MPa and a room temperature self-healing efficiency of 100%. Chinese invention patent application CN 117924647 A discloses a preparation method and application of a polyurethane and polyurethane-based ion conductive elastomer. By introducing the interaction force of double dynamic covalent bonds and non-covalent bonds, multiple multi-level hydrogen bonds, disulfide bonds and dynamic DA bonds are simultaneously introduced into the polyurethane system to prepare a polyurethane-based ion conductive elastomer with good mechanical properties, ideal ionic conductivity, excellent self-healing ability and recyclability. Moreover, the polyurethane-based ion conductive elastomer has excellent sensing stability and sensitivity, and can be applied to highly sensitive flexible sensors to play a role in human motion monitoring. However, the comprehensive performance of the above-mentioned elastomer needs to be improved.

[0004] The present invention aims at the problem of how to simultaneously realize the high performance and conductive functionalization of self-healing elastomers, introduces lithium ions into polyurethane-urea elastomers, forms ionic coordination between lithium ions and oxygen atoms of carbonyl groups and cation-π interaction between lithium ions and benzene rings, constructs a lithium ion-based conductive channel in the elastomer system, and then combines the multiple hydrogen bonds formed between polymer segments to construct a polymer network with multiple non-covalent interactions, and successfully prepares a polyurethane-urea conductive elastomer material with high conductivity, high strength, excellent resilience, self-healing performance, transparency and stable stretching sensing performance. The material of the present invention can be used as an excellent stretchable conductor material, and has great application potential in monitoring human dynamic activities, monitoring mechanical movement and human-computer interaction processes, and at the same time provides a way of thinking for preparing functional self-healing elastomer materials. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a polyurethane-urea conductive elastomer and a preparation method thereof with high conductivity, high strength, excellent resilience, self-healing performance, transparency and stable tensile sensing performance (i.e., a high-performance transparent self-healing conductive elastomer and a preparation method thereof). The present invention uses polyester diol, diisocyanate and dihydrazide containing a benzene ring to undergo polymerization reaction, and then adds lithium bis(trifluoromethanesulfonyl)imide to construct a multiple non-covalent interaction, including the ionic coordination of lithium ions with the oxygen atoms of the carbonyl group, the cation-π interaction of lithium ions with the benzene ring and multiple hydrogen bonds, and finally obtains a series of high-performance conductive elastomer materials. The polyurethane-urea conductive elastomer prepared by the method of the present invention exhibits very excellent comprehensive properties: high tensile strength (68.7MPa), excellent resilience, high transmittance (91.01%), high ionic conductivity (1.32×10 -5 S / cm), excellent self-healing ability and stable stretch sensing performance.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a high-performance transparent self-healing conductive elastomer comprises the following steps:

[0008] 1) reacting polyester diol with diisocyanate under the action of a catalyst to obtain an isocyanate-terminated polyurethane prepolymer;

[0009] 2) mixing the benzene ring-containing dihydrazide with the polyurethane prepolymer, and performing a chain extension reaction to obtain a polyurethane-urea reaction solution;

[0010] 3) mixing lithium bis(trifluoromethanesulfonyl)imide and the polyurethane-urea reaction solution, and curing and molding to obtain a polyurethane-urea conductive elastomer.

[0011] The polyester diol is one or two of poly(1,4-butylene adipate) diol (PBA), polycaprolactone diol (PCL) and polycarbonate diol (PCDL).

[0012] Step 1) The number average molecular weight of the polyester diol is 650-3000 g / mol.

[0013] In step 1), the diisocyanate is one or more of 4,4'-dicyclohexylmethane diisocyanate (HMDI) (i.e., dicyclohexylmethane diisocyanate), isophorone diisocyanate (IPDI), 4,4'-diphenylmethane diisocyanate (MDI), 1,6-hexamethylene diisocyanate (HDI) and toluene diisocyanate (TDI).

[0014] The molar ratio of isocyanate in the diisocyanate to hydroxyl in the polyester diol is 1.9 / 1 to 2.5 / 1.

[0015] Step 1) The catalyst is one or more of triethylamine, stannous octoate or dibutyltin dilaurate, and the amount of the catalyst added is 0.5% to 1% by weight of the polyester diol.

[0016] Step 1) The polyester diol is dehydrated before the reaction; the polyester diol and diisocyanate are reacted under the protection of N2 atmosphere.

[0017] Step 1) The reaction temperature is 60-80°C and the reaction time is 3-5h.

[0018] Step 2) the dihydrazide is one of isophthalic acid dihydrazide or terephthalic acid dihydrazide.

[0019] Step 2) The molar ratio of the amino group in the dihydrazide chain extender to the isocyanate group in the diisocyanate is (0.9-1.5): (1.9-2.5).

[0020] In step 2), an organic solvent is added during the chain extension reaction, or the organic solvent is mixed with the polyurethane prepolymer and then mixed with dihydrazide to carry out the chain extension reaction.

[0021] In step 2), the organic solvent is one or more of N,N-dimethylformamide and N,N-dimethylacetamide.

[0022] The usage ratio of the organic solvent to hydrazide is (30-60) mL:0.01 mol.

[0023] The temperature of the chain extension reaction in step 2) is 30-50° C., and the reaction time is 4-9 hours.

[0024] The molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polyester diol in step 3) is (1-1.75):1.

[0025] The curing molding conditions in step 3) are to place the reacted system in a mold, remove the organic solvent, and then heat treat at 60-100° C. for 6-12 hours.

[0026] The conductive elastomer is a conductive elastomer film.

[0027] The repair method of the high-performance transparent self-healing conductive elastomer film is: treating the broken or cracked film at 60 to 80° C. for 24 to 48 hours.

[0028] The principle that the high-performance transparent self-healing conductive elastomer film of the present invention has very excellent comprehensive performance is: through polyester diol, diisocyanate, two different dihydrazide chain extenders for polymerization reaction, and then adding lithium bis(trifluoromethanesulfonyl)imide, a multiple non-covalent interaction is constructed, including the ionic coordination of lithium ions and the oxygen atoms of carbonyl groups, the cation-π interaction of lithium ions and benzene rings, and multiple hydrogen bonds. Multiple non-covalent interactions play an important role in the mechanical properties, electrical conductivity, resilience and self-healing properties of conductive elastomers. For mechanical properties, the higher the multiple non-covalent interactions between polymer chains in the system, the greater the stress required for the polymer chain segments to be stretched, and the greater the corresponding tensile strength. For electrical conductivity, the coordination of lithium ions with the oxygen atoms of carbonyl groups and the cation-π interaction with benzene rings construct enough conductive paths, which promote the migration of lithium ions under the action of external electric fields, giving the elastomer material good electrical conductivity. For the resilience performance, the formation of multiple non-covalent interactions will increase the degree of physical cross-linking of the polymer network, which will limit the residual orientation of the molecular chains and give the elastomeric material good resilience performance. For the self-healing performance, the increase in temperature will cause the dissociation of multiple non-covalent interactions, and the ion coordination, cation-π interaction and multiple hydrogen bonding in the system will be continuously and dynamically exchanged until a dynamic equilibrium is reached, so that the polymer network is reconstructed and the elastomeric material has excellent self-healing performance.

[0029] Compared with the prior art, the advantages of the present invention are:

[0030] 1) The polyurethane-urea film prepared by the present invention has high conductivity, high strength, excellent resilience, self-healing performance, transparency and stable tensile sensing performance. The tensile strength reaches 68.7MPa and the ionic conductivity reaches 1.32×10 - 5S / cm, and has high light transmittance (91.01%), and has excellent resilience and self-healing ability. In addition, the elastomer also has excellent tensile sensing performance and can be used as a stretchable conductor in strain sensors. It has great application value in monitoring human joint activities, mechanical movements, and human-computer interaction processes. For mechanical movements with large deformations and large driving forces, the stretchable conductor materials used for monitoring are more prone to breakage, and the conductive elastomer material prepared by the present invention has high strength, self-healing properties and stable tensile sensing performance, which is more suitable for monitoring this type of movement than other materials.

[0031] 2) The synthesis conditions of the present invention are mild, the preparation process is simple, and the raw materials are easily available. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a stress-strain curve diagram of Examples 1 to 4 and a comparative example;

[0033] Figure 2 is the ionic conductivity curve of Examples 1 to 4;

[0034] Figure 3 is a comparison diagram of ionic conductivity between Example 4 and the comparative example;

[0035] Figure 4 are cyclic loading-unloading tensile curves of Examples 1 to 4 at 50% and 200% strains; a and e are for Example 1; b and f are for Example 2; c and g are for Example 3; d and h are for Example 4;

[0036] Figure 5 is a light transmittance curve of Example 1 in the visible light range;

[0037] Figure 6 is a stress-strain curve diagram of Examples 1 to 4 after repair;

[0038] Figure 7 is a comparison chart of ionic conductivity before and after repair of Examples 1 to 4;

[0039] Figure 8 is a tensile sensing performance diagram of Example 1;

[0040] Fig. 9 This is a diagram of sensor signal changes in Example 1 applied to human joint motion monitoring and mechanical joint motion monitoring. DETAILED DESCRIPTION

[0041] In order to better illustrate the present invention, the technical solution of the present invention is further described below in conjunction with specific embodiments and drawings, but the scope of protection of the present invention is not limited thereto.

[0042] Example 1

[0043] A method for preparing a high-performance transparent self-healing conductive elastomer film comprises the following steps:

[0044] 5.27 g of 4,4-dicyclohexylmethane diisocyanate and 10 g of poly(1,4-butylene adipate) diol with a molecular weight of 1000 were mixed and stirred evenly, 0.1 g of dibutyltin dilaurate was added, and the mixture was heated and stirred in an oil bath at 80° C. for 3 h to obtain a prepolymer; 1.94 g of isophthalic acid hydrazide was added to the prepolymer, and the mixture was reacted at 45° C. for 8 h, during which 40 ml of N,N-dimethylacetamide was added for dilution; 2.87 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was then dissolved in 6 ml of N,N-dimethylacetamide (DMAC), and the mixture was added to the reaction solution and stirred for 2 h; the reaction product was then cast into a polytetrafluoroethylene mold, the organic solvent used was removed in a vacuum oven at 40 to 60° C., and then the polyurethane-urea film was obtained by treating the prepolymer in a forced air oven at 80° C. for 12 h.

[0045] Example 2

[0046] A method for preparing a high-performance transparent self-healing conductive elastomer film comprises the following steps:

[0047] 5.27 g of 4,4-dicyclohexylmethane diisocyanate and 10 g of poly(1,4-butylene adipate) diol with a molecular weight of 1000 were mixed and stirred evenly, 0.1 g of dibutyltin dilaurate was added, and the mixture was heated and stirred in an oil bath at 80° C. for 3 h to obtain a prepolymer; 1.94 g of isophthalic acid hydrazide was added to the prepolymer, and the mixture was reacted at 45° C. for 8 h, during which 40 ml of N,N-dimethylacetamide was added for dilution; then 3.59 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dissolved in 8 ml of N,N-dimethylacetamide (DMAC), and the mixture was added to the reaction solution and stirred for 2 hours; the reaction product was then cast into a polytetrafluoroethylene mold, the organic solvent used was removed in a vacuum oven at 40 to 60° C., and then the polyurethane-urea film was obtained by treating the prepolymer in a blast oven at 80° C. for 12 h.

[0048] Example 3

[0049] A method for preparing a high-performance transparent self-healing conductive elastomer film comprises the following steps:

[0050] 5.27 g of 4,4-dicyclohexylmethane diisocyanate and 10 g of poly(1,4-butylene adipate) diol with a molecular weight of 1000 were mixed and stirred evenly, 0.1 g of dibutyltin dilaurate was added, and the mixture was heated and stirred in an oil bath at 80° C. for 3 h to obtain a prepolymer; 1.94 g of isophthalic acid hydrazide was added to the prepolymer, and the mixture was reacted at 45° C. for 8 h, during which 40 ml of N,N-dimethylacetamide was added for dilution; 4.31 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was then dissolved in 10 ml of N,N-dimethylacetamide (DMAC), and the mixture was added to the reaction solution and stirred for 2 h; the reaction product was then cast into a polytetrafluoroethylene mold, the organic solvent used was removed in a vacuum oven at 40 to 60° C., and then the polyurethane-urea film was obtained by treating the prepolymer in a blast oven at 80° C. for 12 h.

[0051] Example 4

[0052] A method for preparing a high-performance transparent self-healing conductive elastomer film comprises the following steps:

[0053] 5.27 g of 4,4-dicyclohexylmethane diisocyanate and 10 g of poly(1,4-butylene adipate) diol with a molecular weight of 1000 were mixed and stirred evenly, 0.1 g of dibutyltin dilaurate was added, and the mixture was heated and stirred in an oil bath at 80° C. for 3 h to obtain a prepolymer; 1.94 g of isophthalic acid hydrazide was added to the prepolymer, and the mixture was reacted at 45° C. for 8 h, during which 40 ml of N,N-dimethylacetamide was added for dilution; then 5.02 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dissolved in 12 ml of N,N-dimethylacetamide (DMAC), and the mixture was added to the reaction solution and stirred for 2 hours; the reaction product was then cast into a polytetrafluoroethylene mold, the organic solvent used was removed in a vacuum oven at 40 to 60° C., and then the polyurethane-urea film was obtained by treating the prepolymer in a blast oven at 80° C. for 12 h.

[0054] Comparative Example

[0055] A method for preparing a high-performance transparent self-healing conductive elastomer film comprises the following steps:

[0056] 5.27 g of 4,4-dicyclohexylmethane diisocyanate and 10 g of poly(1,4-butylene adipate) diol with a molecular weight of 1000 were mixed and stirred evenly, 0.1 g of dibutyltin dilaurate was added, and the mixture was heated and stirred in an oil bath at 80° C. for 3 h to obtain a prepolymer; 1.74 g of adipic acid dihydrazide was added to the prepolymer, and the mixture was reacted at 45° C. for 8 h, during which 30 ml of N,N-dimethylacetamide was added for dilution; 4.31 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was then dissolved in 10 ml of N,N-dimethylacetamide (DMAC), and the mixture was added to the reaction solution and stirred for 2 h; the reaction product was then cast into a polytetrafluoroethylene mold, the organic solvent used was removed in a vacuum oven at 40 to 60° C., and then the polyurethane-urea film was obtained by treating the prepolymer in a blast oven at 80° C. for 12 h.

[0057] The tensile properties test method of the high-performance transparent self-healing conductive elastomer film: the tensile strength and elongation at break are tested using a tensile testing machine.

[0058] Cyclic tensile properties test method for high-performance transparent self-healing conductive elastomer films: at 50 mm / min -1 Cyclic tensile tests were performed at a constant loading-unloading rate to evaluate the elastic recovery of the conductive elastomer. During the test, the specimens were stretched to produce 50% and 200% strains and then released immediately to complete stress unloading. After unloading, wait 30 seconds to enter the next loading-unloading cycle, and cyclic stretching was repeated 5 times.

[0059] The repair method of the high-performance transparent self-healing conductive elastomer film is as follows: the film is cut into dumbbell-shaped or rectangular splines, the splines are cut with a scalpel, placed at 60 to 80°C for 24 to 48 hours, and then the tensile strength and ionic conductivity are tested.

[0060] The conductivity test method of the high-performance transparent self-healing conductive elastomer film is: use a resistive digital source meter to test the ionic conductivity of the elastomer. The shape of the sample is a cuboid, and the sample size is 10mm×10mm×1mm. After wrapping the left and right ends with copper foil, clamp the test line interface on the copper foil to test the resistance of the sample. The ionic conductivity is calculated by the following formula:

[0061]

[0062] Where σ is the conductivity, L is the sample length, R is the resistance of the sample, and S is the sample cross-sectional area.

[0063] The stretch sensing performance of the high-performance transparent self-healing conductive elastomer film was tested by assembling the ionic elastomer and the stretchable conductor material into a strain resistive sensor. The sample was wrapped with a copper wire and connected to a resistive digital source meter at a speed of 50 mm min.-1 The ion elastomer was subjected to different tensile strains at different stretching rates, and the change in its relative resistance was tested during the process. The ion elastomer was also worn on different joints of the human body and a robotic arm, and the change in its relative resistance was tested using a resistive digital source meter as the fixed joints moved and the machine moved.

[0064] The comprehensive performance of the above embodiments and comparative examples were tested respectively, and the results are shown in Table 1, Table 2 and Figure 1-Figure 9 shown.

[0065] Figure 1 is a stress-strain curve diagram of Examples 1 to 4 and a comparative example; Figure 2 is the ionic conductivity curve of Examples 1 to 4; Figure 3 is a comparison diagram of ionic conductivity of Example 4 and the comparative example; Figure 4 are cyclic loading-unloading tensile curves of Examples 1 to 4 at 50% and 200% strains; Figure 5 is a light transmittance curve of Example 1 in the visible light range; Figure 6 is a stress-strain curve diagram of Examples 1 to 4 after repair;

[0066] Figure 7 is a comparison chart of ionic conductivity before and after repair of Examples 1 to 4; Figure 8 is a tensile sensing performance diagram of Example 1; Fig. 9 This is a diagram of sensor signal changes in Example 1 applied to human joint motion monitoring and mechanical joint motion monitoring.

[0067] from Figure 1 It can be seen that the prepared conductive elastic film has ultra-high tensile properties, the tensile strength of each embodiment is in the range of 53.3MPa-68.7MPa, the highest is 68.7MPa, and the elongation at break is in the range of 682%-807%.

[0068] from Figure 2 It can be seen that the ionic conductivity of the conductive elastomer is 2.81×10 -6 S / cm-1.32×10 -5 In the range of 1000 S / cm, as the amount of lithium salt added increases, the ionic conductivity of the conductive elastomer film shows an upward trend.

[0069] from Figure 3 As shown, the conductivity of Example 4 is much higher than that of the comparative example.

[0070] Depend on Figure 4As shown, the stress-strain curves of the five loading-unloading processes of Example 3 are almost overlapped, and the residual strain of Example 3 is the smallest when the stress value returns to zero, indicating that the tensile resilience performance of Example 3 is the best. On the contrary, the stress-strain curves of the loading-unloading processes of the other examples cannot be overlapped, and when the stress value returns to zero, the residual strain values ​​of the three examples are in the order of Example 2 < Example 1 < Example 4, indicating that with the increase in the amount of lithium salt added, the excellence of the tensile resilience performance of the conductive elastomer film first increases and then decreases.

[0071] Depend on Figure 5 As shown, the transmittance of Example 1 is greater than 90% on average, proving that the prepared conductive elastic film has high transparency.

[0072] From Table 1, Figure 6 and Figure 7 As shown, after the samples of each embodiment were repaired after being damaged, the mechanical properties and electrical conductivity were restored. The tensile strength of the four embodiments was restored to more than 83% of the original, and the embodiment with the best repair ability could be restored to about 95% of the original. Moreover, the ionic conductivity of the four embodiments was almost the same as before repair, indicating that the prepared polyurethane-urea film has excellent self-healing properties.

[0073] Depend on Figure 8 As shown, as the strain value increases, the relative resistance change value of Example 3 increases in a linear manner, and the rate of change of the relative resistance is equal to the slope of the straight line, which is called the GF factor, and the GF factor reaches 1.17. By performing four cyclic stretching tests on Example 3 at strains of 25%, 50%, 75% and 100%, the graphs of the relative resistance change in each cyclic test under the same strain are almost completely consistent, indicating that the elastomer has good tensile sensing stability under different strains. In order to further test whether the conductive elastomer has long-term tensile sensing stability, Example 3 was subjected to 1000 cyclic stretching tests at 50% strain. The results show that the graphs of the relative resistance change of the elastomer in 1000 cycles are similar, and there are only small errors between the graphs, indicating that the conductive elastomer has excellent sensing stability and reliability, which is derived from the excellent tensile resilience and stable high ionic conductivity of the elastomer.

[0074] Depend on Fig. 9As shown, the conductive elastomer is actually applied to strain sensors and fixed on different parts of the human body and on a robotic arm to monitor different human body movements and mechanical motion processes. For the extension and retraction movements of the human fingers, elbows and knees, different extension and retraction movements correspond to a specific relative resistance change graph, and specific extension and retraction movements can be distinguished and monitored based on the specific graph. The relative resistance changes corresponding to the four extension and retraction movements are basically consistent within four cycles, indicating that the monitoring process of the sensor has good stability and reliability. For the extension and retraction movements of the robotic arm joints with large strain levels and driving forces, the monitoring process of the sensor also has good stability and reliability, and the ion conductive elastomer with high mechanical properties has a greater tolerance for mechanical movements with large driving forces and is not easily damaged during use.

[0075] Table 1 Tensile properties and repair efficiency after repair in each embodiment

[0076]

[0077] Table 2 Transmittance of each embodiment

[0078]

[0079] From Table 1, Table 2 and Figures 1 to 9 It can be seen that the elastic film of the present invention has good self-healing performance, mechanical properties, resilience, conductivity and transmittance. The comprehensive performance is better.

[0080] The above embodiment is an embodiment of the present invention for preparing a high-performance transparent self-healing conductive elastomer film, but the present invention is not limited to the above embodiment, and the implementation mode of the present invention is not limited to the above embodiment. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance transparent self-healing conductive elastomer, characterized in that: The following steps are involved: 1) reacting polyester diol with diisocyanate under the action of a catalyst to obtain an isocyanate-terminated polyurethane prepolymer; 2) mixing a benzene ring-containing dihydrazide with a polyurethane prepolymer, and performing a chain extension reaction to obtain a polyurethane-urea reaction solution; the dihydrazide is one or more of isophthalic acid dihydrazide or terephthalic acid dihydrazide; 3) mixing lithium bis(trifluoromethanesulfonyl)imide and the polyurethane-urea reaction solution, and curing and molding to obtain a polyurethane-urea conductive elastomer.

2. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 1, characterized in that: Step 2) The molar ratio of the amino group in the dihydrazide to the isocyanate group in the diisocyanate is (0.9-1.5): (1.9-2.5); The molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polyester diol in step 3) is (1-1.75):

1.

3. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 1, characterized in that: The molar ratio of isocyanate in the diisocyanate to hydroxyl in the polyester diol is 1.9 / 1 to 2.5 / 1; The polyester diol is one or more of poly(1,4-butylene adipate diol), polycaprolactone diol and polycarbonate diol; Step 1) The number average molecular weight of the polyester diol is 650-3000 g / mol; In step 1), the diisocyanate is one or more of 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,6-hexamethylene diisocyanate and toluene diisocyanate.

4. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 1, characterized in that: Step 1) The reaction temperature is 60-80°C and the reaction time is 3-5h; The temperature of the chain extension reaction in step 2) is 30-50°C, and the reaction time is 4-9h; In step 2), an organic solvent is added during the chain extension reaction, or the organic solvent is mixed with the polyurethane prepolymer and then mixed with dihydrazide to carry out the chain extension reaction.

5. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 4, characterized in that: Step 2) the organic solvent is one or more of N,N-dimethylformamide and N,N-dimethylacetamide; The usage ratio of the organic solvent to dihydrazide is (30-60) mL:0.01 mol.

6. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 1, characterized in that: Step 1) The catalyst is one or more of triethylamine, stannous octoate or dibutyltin dilaurate, and the amount of the catalyst added is 0.5% to 1% by weight of the polyester diol; Step 1) The polyester diol is dehydrated before the reaction; the polyester diol and diisocyanate are reacted under the protection of N2 atmosphere; The curing molding conditions in step 3) are to place the reacted system in a mold, remove the organic solvent, and then heat treat at 60-100° C. for 6-12 hours.

7. The method for preparing a high-performance transparent self-healing conductive elastomer according to claim 1, characterized in that: The lithium bis(trifluoromethanesulfonyl)imide is first mixed with an organic solvent and then added to the polyurethane-urea reaction solution; the organic solvent is one or more of N,N-dimethylformamide and N,N-dimethylacetamide; The molding refers to solidification into a film shape.

8. A high-performance transparent self-healing conductive elastomer obtained by the preparation method according to any one of claims 1 to 7.

9. The use of the high-performance transparent self-healing conductive elastomer according to claim 8, characterized in that: The high-performance transparent self-healing conductive elastomer is applied to strain sensors and stretchable conductor materials.

10. The use according to claim 9, characterized in that: The high-performance transparent self-healing conductive elastomer is used to prepare products for monitoring human joint activities, mechanical movements and / or human-computer interaction processes.

Citation Information

Patent Citations

  • Preparation method and application of multi-hydrogen-bond-network-based self-repairing high-transparency conductive elastomer

    CN116496436A

  • Preparation method and application of polyurethane and polyurethane-based ionic conductive elastomer

    CN117924647A

  • Conductive self-repairing poly (urethane-amide) as well as preparation method and application thereof

    CN116715824A

  • Ultra-high-performance transparent self-repairing polyurethane-urea film capable of being recycled repeatedly and preparation method of ultra-high-performance transparent self-repairing polyurethane-urea film

    CN117624538A

  • Preparation method and application of high-strength and high-toughness polyurethane and self-repairing polyurethane-based ionic conductive elastomer

    CN118184953A

Cited By

  • High-strength knittable conductive hydrophobic polyurethane eutectic gel fiber and preparation method thereof

    CN119507077A

  • A high-strength, braidable, conductive hydrophobic polyurethane eutectic gel fiber and a method of making the same

    CN119507077B

  • Tough polyurethane ionic gel based on hard segment reinforcement and preparation method thereof

    CN120005233A